2016
DOI: 10.1007/s10971-016-4109-x
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric investigation of high density polyethylene loaded by ZnO nanoparticles synthesized by sol–gel route

Abstract: Zinc oxide nanoparticles (ZnO NPs), with wurtzite structure, were synthesized using sol-gel route. Both the microstructure and morphology of the synthesized ZnO NPs were examined using X-ray diffraction, Fourier transform infrared and high-resolution transmission electron microscopy. The synthesized ZnO NPs up to 5 wt% were introduced to high density polyethylene (HDPE) using melt blending technique. The dielectric properties of the fabricated HDPE/ZnO nanocomposites were studied by measuring the dc dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…The C=O two asymmetric and symmetric stretching bands at 1430 and 1640 cm −1 are resulting from the zinc acetate in the samples. The absorption band that appears at about 440 cm −1 can be assigned to the ZnO stretching modes [ 36 ]. The ZnO stretching mode is showing small changes which is reflecting on the unpronounced changes seen in the volumes of ZnO cell.…”
Section: Resultsmentioning
confidence: 99%
“…The C=O two asymmetric and symmetric stretching bands at 1430 and 1640 cm −1 are resulting from the zinc acetate in the samples. The absorption band that appears at about 440 cm −1 can be assigned to the ZnO stretching modes [ 36 ]. The ZnO stretching mode is showing small changes which is reflecting on the unpronounced changes seen in the volumes of ZnO cell.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement in DBS could be explained by the effect of interaction zones . When the filler is added to the matrix, the surface area of particles increase and the interfacial area increase leading to high volume of interaction zones.…”
Section: Resultsmentioning
confidence: 99%
“…It is fundamentally influenced by cohesive energy density and the free volume or mobility of the polymer . Researcher reported that an enhancement in DBS of composites by applying ZnO/HDPE composites and OMMT/LLDPE nanocomposites . A good insulation should have high flame retardancy to minimize the damage during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were labeled according to 0, 0.5, 0.7, 1.0, and 3.0 wt% percentages, as PS0, PS0.5, PS0.7, PS1.0 and PS3.0, respectively. ZnO nanocrystals were obtained after calcination that was done at 600 °C for 6 h, The structure of the obtained final product of ZnO nanopowders was examined and confirmed by X-ray diffraction (XRD) using -ray diffractometer (PANalytical X’Pert PRO MRD X with Cu Kα radiation source (PANalytical Inc., MA, USA), field emission scanning electron microscope and Fourier transform infrared (FTIR) according to a previous study [ 8 ]. The thermogravimetry (TG) analysis for pure PS and the PS/ZnO nanocomposite films were carried out using a Shimadzu TGA-50H instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Several properties of the polymers have been tuned by proper type and/or amount of nanoparticles that were used as polymers fillers. The incorporation of the inorganic nanomaterials such as ZnO nanoparticles into the organic polymer matrix resulted in polymer/ZnO nanocomposites that had excellent magnetic, mechanical and high thermal stability properties [ 5 , 8 , 9 , 10 ]. Enhancing the thermal stability of the nanocomposites is a crucial aspect for many of their industrial applications [ 7 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%